Protective effect of extractive and biotechnological chondroitin in insulin amyloid and advanced glycation end product‐induced toxicity. Issue 4 (7th September 2018) - Iannuzzi, Clara; Borriello, Margherita; D'Agostino, Antonella; Cimini, Donatella; Schiraldi, Chiara; Sirangelo, Ivana
Abstract: Glycosaminoglycans are extracellular matrix components related to several biological functions and diseases. Chondroitin sulfate is a sulphated glycosaminoglycan synthesized as part of proteoglycan molecules. They are frequently associated with amyloid deposits and possess an active role in amyloid fibril formation. Recently, a neuroprotective effect of extracellular matrix components against amyloid toxicity and oxidative stress has been reported. Advanced glycation end products (AGEs), the end products of the glycation reaction, have been linked to amyloid‐based neurodegenerative disease as associated with oxidative stress and inflammation. In this study we have analyzed the effect of chondroitin sulfate isolated from different species, in comparison with a new biotechnological unsulfated chondroitin, in the amyloid aggregation process of insulin, as well as the ability to prevent the formation of AGEs and related toxicity. The results have showed a determining role of chondroitin sulfate groups in modulating insulin amyloid aggregation. In addition, both sulfated and unsulfated chondroitins have shown protective properties against amyloid and AGEs‐induced toxicity. These data are very relevant as a protective effect of these glycosaminoglycans in the AGE‐induced toxicity was never observed before. Moreover, considering the issues related to the purity and safety of chondroitin from natural sources, this study suggests a new potential application for the biotechnological chondroitin.